A chromosomal-level genome assembly of Kibakoganea sinica, Bouchard, 2005 (Coleoptera: Scarabaeidae) - Ming Zhu; Jingjing Zhang; Junhui Yan; Yanting Han (Scientific Data)
Abstract The family Scarabaeidae is one of the largest and most ecologically significant groups within the order Coleoptera, comprising over 35,000 described species. However, the limited availability of high-quality genome assemblies has hindered comprehensive studies on their ecology and evolutionary biology. In this study, we present a high-quality, chromosome-level genome assembly of Kibakoganea sinica, generated by integrating PacBio HiFi, Illumina, and Hi-C sequencing data. The final assembly spans 601.44 Mb, comprising 23 scaffolds (scaffold N50: 60.23 Mb) and 70 contigs (contig N50: 24.49 Mb), with 99.57% of the total assembly (598.84 Mb) successfully anchored to 10 chromosomes. BUSCO analysis (n = 1,367) indicates a high level of completeness, with 99.2% of genes detected: 95.2% as single-copy and 4.0% as duplicated. Repetitive elements account for 44.43% (267.24 Mb) of the genome, and a total of 12,940 protein-coding genes were predicted. This chromosome-scale genome assembly provides a foundational resource for future research into the biology and adaptation of Scarabaeidae.